Lexical Errors Found in Subtitling Projects of EFL Learners of University of Lancang Kuning - Destina Kasriyati; Siti Rafiah; Herdi Herdi; M. Fadhly Farhy Abbas (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2019)
The phenomenon of the study is some students wrongly order the word in a sentence as the result of word by word translation and they translate it using translation machine like Google translate so that it is still has an errors in sentence or word. By doing the project uploaded as subtitle in form of video and music in students’ You Tube channel, so around the world see it and become evaluation to the next translator become a good translator. The research aimed to find out the common lexical errors in subtitling projects at the eighth semester students of English Education Department. The research design was descriptive quantitative. Subject the research was 20 students. The instrument was documentation. From the data analysis by rater’s one, it was found that students made lexical error was 136 cases included in semantic confusion was 44 cases with percentages 32.35% was the common lexical error. From the rater’s two was 109 lexical errors still with semantic confusion was 40 cases with percentage 36.69%. It means that the students had enough English vocabulary but they do not know the usage of words in sentences when translate it. Also, it means that students need more practice in translation because of some errors still happen.